Numerical modeling of explosives and propellants - Mader, Charles L. (CRC Press, 2008)
Numerical Modeling of Explosives and Propellants, Third Edition provides a complete overview of this rapidly emerging field, covering basic reactive fluid dynamics as well as the latest and most complex methods and findings. It also describes and evaluates Russian contributions to the experimental explosive physics database, which only recently have become available.